Automated Assessment of Left Ventricular Function and Mass Using Heart Deformation Analysis: Initial Experience in 160 older adults - Lin, Kai (Acad Radiol, 2015)
OBJECTIVE: To assess the performance of automated quantification of left ventricular function and mass based on heart deformation analysis (HDA) in asymptomatic older adults MATERIALS AND METHODS: This study complied with HIPAA regulations. Following the approval of the institutional review board (IRB), 160 asymptomatic older participants were recruited for cardiac MRI including two-dimensional (2D) cine images covering the entire left ventricle (LV) in short-axis view. Data analysis included the calculation of left ventricular ejection fraction (LVEF), mass (LVM) and cardiac output (CO) using HDA and standard global cardiac function analysis (delineation of end systolic and diastolic LV epi- and endo-cardial borders). The agreement between methods was evaluated using intra-class correlation coefficient (ICC) and coefficient of variation (CoV). RESULTS: HDA had a shorter processing time than standard method (1.5 ± 0.3 minute/case vs. 5.8 ± 1.4 minute/case, p < 0.001). There was good agreement for LVEF (ICC = 0.552, CoV = 10.5%), CO (ICC = 0.773, CoV = 13.5%) and LVM (ICC = 0.859, CoV = 14.5%) acquired with standard method and HDA. There was a systemic bias towards lower LVEF (62.8% ± 8.3% vs.69.3% ± 6.7%, p < 0.001) and CO (4.4 ± 1.0 L/minute vs. 4.8 ± 1.3 L/minute, p < 0.001) by HDA compared to the standard technique. Conversely, HDA overestimated LVM (114.8 ± 30.1g vs. 100.2 ± 29.0g, p < 0.001) as compared to the reference method. CONCLUSION: HDA has the potential to measure LVEF, CO, and LVM without the need for user interaction based on standard cardiac 2D Cine images.